2001
DOI: 10.1177/175899830100600302
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin receptors in Dupuytren's tissue: Implications for the pharnnacological treatment of Dupuytren's disease

Abstract: The role of Angiotensin II as a pro-fibrotic mediator has been established in models of cardiac, hepatic and renal fibrosis. The administration of Angiotensin-Converting Enzyme (ACE) – inhibitors to these models results in a reduction in the myofibroblast population and collagen synthesis. In rodent excisionat wound-healing experiments, an ACE inhibitor reduced the rate of wound contraction, collagen deposition and angiogenesis. Using immunohistochemistry, the presence of Angiotensin I receptors was identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…These focused on the myofibroblasts and yielded contradictory results. McKirdy et al 27 have demonstrated the presence of the ATIIR1 on the myofibroblasts, whereas Stephen 28 has found limited expression of ATIIR1 and a much wider distribution of ATIIR2. Rayan et al 29 show contraction in cultured DD myofibroblasts treated with ATII.…”
Section: Discussionmentioning
confidence: 99%
“…These focused on the myofibroblasts and yielded contradictory results. McKirdy et al 27 have demonstrated the presence of the ATIIR1 on the myofibroblasts, whereas Stephen 28 has found limited expression of ATIIR1 and a much wider distribution of ATIIR2. Rayan et al 29 show contraction in cultured DD myofibroblasts treated with ATII.…”
Section: Discussionmentioning
confidence: 99%
“…McKirdy et al [22] identified the presence of AT1 receptors using immunohistochemistry in Dupuytren's disease. They found that these receptors were colocalised with areas of myofibroblast expression, which has implications for the potential of pharmacological regulation using ACE-inhibitors to modulate contracture disease processes.…”
Section: Angiotensin and Its Role In Wound Healingmentioning
confidence: 99%